Gastrointestinal symptoms in 342 patients with Fabry disease: prevalence and response to enzyme replacement therapy. - Hoffmann, B; Schwarz, M; Mehta, A; Keshav, S (2007)
BACKGROUND and AIMS: Fabry disease is an X-linked deficiency of alpha-galactosidase A, resulting in lysosomal deposition of globotriaosylceramide in nearly all tissues. The disease frequently causes diarrhea and abdominal pain, which are assumed to arise from malfunction of enteric neurons and which mimic diarrhea-predominant irritable bowel syndrome (IBS). There are limited data about the prevalence and nature of gastrointestinal symptoms in patients with Fabry disease and the response to enzyme replacement therapy (ERT) in large cohorts. The aims of this study were to evaluate the nature and prevalence of gastrointestinal symptoms and their impact on health-related quality of life (HRQoL) in patients with Fabry disease and to analyze changes after 12 and 24 months of treatment with agalsidase alfa. METHODS: Information about gastrointestinal symptoms was obtained from regular interviews before and during the time of ERT. Data on HRQoL were collected by using the EQ-5D questionnaire. RESULTS: The overall prevalence of gastrointestinal symptoms was 52%, with abdominal pain and diarrhea being most frequent. Female patients were more frequently affected than male patients, and there was a high prevalence in children (abdominal pain, 49.3%; diarrhea 25.4%). ERT with agalsidase alfa reduced the prevalence of abdominal pain, with a statistically significant decrease in male patients and in children after 12 months of treatment. CONCLUSIONS: The gastrointestinal symptomatology of Fabry disease is very similar to diarrhea-predominant IBS; however, pathophysiologic similarities remain to be elucidated. ERT reduced the prevalence of gastrointestinal symptoms in Fabry disease, particularly in children and male patients.